Pengaruh Terapi Murotal terhadap Perkembangan Motorik Anak Berkebutuhan Khusus “Autis” - Hadrayani, Eka; Muthahharah, Muthahharah; Diana, Nadila; Purnama, Nahdah (Jurnal Gema Keperawatan, 2024)
Autistic children experience complex brain development disorders that affect perception, intention, imagination, feelings with significant obstacles in social interaction, communication, a tendency to obsession with certain activities or objects. They need special educational services to develop their potential. The increasing prevalence of autism in children is a developmental problem that requires attention, and murrotal therapy is one intervention that has been proven to support their development. The aim of this research was to determine the effect of murrotal therapy intervention on the development of autistic children before and after the intervention. The research method used is quantitative with a quasi-experimental one group pretest-posttest design with a duration of around 15–30 minutes, carried out 1–2 times a day, so that children have enough time to absorb and respond to stimuli without being burdened. The research sample was 15 autistic children aged 7-12 years, able to hear and not currently participating in music therapy. The instrument used in this research was the Pre-Developmental Screening. Data were analyzed using the Wilcoxon test. The results showed that there was an influence on fine motor development with a value of p= 0,003, and an influence on gross motor development with a value of p= 0,002. There is a significant influence of Surah Ar Rahman murrotal intervention on the development of autistic children. This therapy can be applied routinely in special schools and home environments as part of a motor development program for autistic children. Schools and educators can integrate murrotal therapy into daily activities as an alternative to support the motor development of children with autism. Parents are expected to support the provision of murrotal therapy at home to strengthen its positive impact on children's development.